The Chemical Interplay between Nitric Oxide and Mitochondrial Cytochrome c Oxidase: Reactions, Effectors and Pathophysiology - Paolo Sarti; Elena Forte; Alessandro Giuffrè; Daniela Mastronicola; Maria Chiara Magnifico; Marzia Arese (International Journal of Cell Biology)
Nitric oxide (NO) reacts with Complex I and cytochrome c oxidase (CcOX, Complex IV), inducing detrimental or cytoprotective effects. Two alternative reaction pathways (PWs) have been described whereby NO reacts with CcOX, producing either a relatively labile nitrite-bound derivative (CcOX-NO2 −, PW1) or a more stable nitrosyl-derivative (CcOX-NO, PW2). The two derivatives are both inhibited, displaying different persistency and O2 competitiveness. In the mitochondrion, during turnover with O2, one pathway prevails over the other one depending on NO, cytochrome c2+ and O2 concentration. High cytochrome c2+, and low O2 proved to be crucial in favoring CcOX nitrosylation, whereas under-standard cell-culture conditions formation of the nitrite derivative prevails. All together, these findings suggest that NO can modulate physiologically the mitochondrial respiratory/OXPHOS efficiency, eventually being converted to nitrite by CcOX, without cell detrimental effects. It is worthy to point out that nitrite, far from being a simple oxidation byproduct, represents a source of NO particularly important in view of the NO cell homeostasis, the NO production depends on the NO synthases whose activity is controlled by different stimuli/effectors; relevant to its bioavailability, NO is also produced by recycling cell/body nitrite. Bioenergetic parameters, such as mitochondrial ΔΨ, lactate, and ATP production, have been assayed in several cell lines, in the presence of endogenous or exogenous NO and the evidence collected suggests a crucial interplay between CcOX and NO with important energetic implications.